An Ixodes scapularis protein required for survival of Anaplasma phagocytophilum in tick salivary glands - Sukumaran, Bindu (The Rockefeller University Press, 2006)
Anaplasma phagocytophilum is the agent of human anaplasmosis, the second most common tick-borne illness in the United States. This pathogen, which is closely related to obligate intracellular organisms in the genera Rickettsia, Ehrlichia, and Anaplasma, persists in ticks and mammalian hosts; however, the mechanisms for survival in the arthropod are not known. We now show that A. phagocytophilum induces expression of the Ixodes scapularis salp16 gene in the arthropod salivary glands during vector engorgement. RNA interference–mediated silencing of salp16 gene expression interfered with the survival of A. phagocytophilum that entered ticks fed on A. phagocytophilum–infected mice. A. phagocytophilum migrated normally from A. phagocytophilum–infected mice to the gut of engorging salp16-deficient ticks, but up to 90% of the bacteria that entered the ticks were not able to successfully infect I. scapularis salivary glands. These data demonstrate the specific requirement of a pathogen for a tick salivary protein to persist within the arthropod and provide a paradigm for understanding how Rickettsia-like pathogens are maintained within vectors.